Environmental risk factors and cancer incidence in rural central Kansas - Romang, Luke David (My University, 2025)
Groundwater contamination is a global concern in agricultural regions and can lead to adverse health effects for affected populations. In central Kansas, three predominantly agricultural counties exhibit notably high cancer incidence rates compared to the state average. This study investigates potential links between land use practices, groundwater contamination, and elevated cancer rates in these counties while also assessing the role of radon exposure. Additionally, we sought to identify factors controlling contaminant occurrence and distribution in local groundwater. We collected 56 groundwater samples, deployed 39 indoor radon tests, and conducted 65 household cancer surveys. A GIS-based buffer analysis using CDL and NLCD land use datasets was performed to explore potential associations between land use and groundwater contamination. Geochemical analyses were used to evaluate possible controls on contaminant occurrence, including pH, redox conditions, and water-rock interactions. Our findings indicate that redox state is the primary control on groundwater geochemistry and contaminant distribution. Evaporation was a key factor influencing groundwater chemistry in Russell County, while water-rock interactions were more significant in Lincoln and Ellsworth County. In the majority of the study area, nitrate and uranium concentrations exceeded EPA and WHO maximum contaminant levels, and 48.7% of radon measurements exceeded the EPA action level of 4 pCi/L. Although no clear correlations were found between agricultural land use and contaminant occurrence, a positive association was observed between open-water land cover and nitrate concentrations. Our cancer data reveals that 64% and 77% of households surveyed in Lincoln and Russell counties, respectively, reported cancer within the household. Additionally, 83% of participants in Lincoln County have a family history of cancer. In Russell County, 6% of cases were in individuals under 20 years old, while in Ellsworth County, 18% were in individuals aged 20-40. This study provides preliminary correlational evidence linking environmental factors to cancer causation and contributes cancer data for the region, offering a glimpse of potential environmental cancers that might guide future studies and provide a framework for future public health guidelines.
Keywords: Groundwater contamination; Cancer incidence; Agricultural land; Radon; Geochemical analysis; Environmental factors